Penerapan Teknologi Digital di Pelabuhan Indonesia untuk Menurunkan Biaya Logistik Nasional - Safuan Safuan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
Indonesian Ports’ fundamental role of digital development is to integrate processes and improve services to be able to compete globally. This research aims to analyze the implementation and development of digitalization in the Port of Indonesia. It is expected to be the reference for digital development in other ports in Indonesia. This research used a qualitative method with a document analysis approach. Document analysis is carried out by collecting data through document review which consists of written sources, images, and monumental works that provides information such as annual reports, materials’ exposure, work plan, company’s regulation, journals, etc. The results show that Indonesian Ports have developed several digital technologies from many aspects; sea, land, and customer. Indonesian Ports could collaborate with the existing ecosystem to compete globally and contribute in decreasing the national logistics cost.